Implementation of Good Corporate Governance in Improving Company Financial Performance (A Case Study of PT. Industri Jamu dan Farmasi Sido Muncul Tbk) - Hartanto, Rudy; Rahayu, Dwi (Insight Management and Business (IMB), 2024)
This study examines the implementation of Good Corporate Governance (GCG) at PT. Industri Jamu dan Farmasi Sido Muncul Tbk and its impact on the company's financial performance. GCG, which encompasses the principles of transparency, accountability, responsibility, independence, and fairness, is implemented to create a transparent and accountable corporate governance system. This research uses a case study approach to analyze various aspects of financial performance such as profitability, liquidity, solvency, and operational efficiency. The results of the study indicate that the implementation of GCG at PT. Sido Muncul has successfully increased stakeholder trust, reduced the risk of fraud, and improved the company's financial performance. This study provides insights into the importance of GCG implementation for enhancing company performance and reputation, and offers a reference for other companies in applying effective GCG practices.